2014
DOI: 10.1177/0148607114546166
|View full text |Cite
|
Sign up to set email alerts
|

How to Promote Bedside Placement of the Postpyloric Feeding Tube

Abstract: Gastric air insufflation seems to be clinically better for promoting bedside placement of postpyloric feeding tubes in adults. Clinicians should no longer use prokinetic agents in pediatric patients or patients without impaired motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 32 publications
(69 reference statements)
0
6
0
1
Order By: Relevance
“…The optimal method of achieving safe and effective postpyloric enteral access at the bedside remains controversial [ 10 ]. Both endoscopic and fluoroscopic assistance are deemed the most effective methods for postpyloric tube placement [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal method of achieving safe and effective postpyloric enteral access at the bedside remains controversial [ 10 ]. Both endoscopic and fluoroscopic assistance are deemed the most effective methods for postpyloric tube placement [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elle peut cependant être discutée en cas d'intolérance digestive, pouvant permettre d'atteindre plus rapidement les objectifs nutritionnels [50] et d'améliorer la tolérance [22]. La technique de pose de la sonde en post-pylorique à l'aveugle semble donner de bons résultats [51]. En cas d'administration médicamenteuse, il faudra vérifier leurs propriétés phamacocinétiques (pouvant impacter l'absorption), et en cas de doute, les médicaments seront administrés en site gastrique.…”
Section: Modes D'administrationunclassified
“…The use of a noninvasive electromagnetic device to place transpyloric feeding tubes has been suggested to be effective in children (64), although in another study it significantly increased the time of placement (65). Several studies showed that the insufflation of 10 mL/kg air in the stomach significantly improves the rate of success without increasing risks (66,67). A recent meta-analysis of all the RCTs both in adults and children concluded that gastric air insufflation seems to be efficient (without reaching significance), whereas clinicians should no longer use prokinetic agents in paediatric patients or patients without impaired motility (66,67).…”
Section: Domperidonementioning
confidence: 99%
“…Several studies showed that the insufflation of 10 mL/kg air in the stomach significantly improves the rate of success without increasing risks (66,67). A recent meta-analysis of all the RCTs both in adults and children concluded that gastric air insufflation seems to be efficient (without reaching significance), whereas clinicians should no longer use prokinetic agents in paediatric patients or patients without impaired motility (66,67). Bedside placement of a postpyloric tube can be safe and effective in infants including preterm and reduce infants' exposure to radiation in comparison to interventional radiology placement (68).…”
Section: Domperidonementioning
confidence: 99%